Determinan Disparitas Pendapatan di Kota Mojokerto - Syamsul Huda (SAFE-Network, 2026)
Income inequality remains one of the major challenges of regional economic development in Indonesia. Despite continuous economic growth, several regions continue to experience unequal income distribution, indicating that economic development has not fully resulted in equitable welfare improvements. This study aims to analyze the effects of educational attainment, regional minimum wages, and unemployment on income inequality in Mojokerto City during the 2017–2022 period. This study employed a quantitative approach using secondary data obtained from Indonesian Bureau of Statistics (BPS). The panel datasets consisted of six cross-sectional units observed over six years (2017–2022), resulting in a total of 36 observations. Panel data regression analysis was applied using model selection procedures through the Chow test and Lagrange Multiplier test. The findings indicate that educational attainment and regional minimum wages have negative and significant effects on income inequality, while unemployment has a positive and significant effect. These results suggest that improving educational quality, maintaining adequate wage policies, and expanding employment opportunities are essential to reducing income disparities and promoting more inclusive regional economic development.